The brand expe-resonance model, a new invention and practical tool of brand experience for fast food industry / Rozita Naina Mohamed … [et al.] - Naina Mohamed, Rozita; Mohd Daud, Norzaidi; Abdul Rahim, Faizah; Musa, Rosidah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Evidently, fast food industry has experienced the fastest growth and contributed economically to the nation. Since the competition is getting stiff, the industry has to precisely understand the consumers’ sensitivity, lifestyle and consumption experience. Notably, brand experience is still new and emerging, attracting a lot of attention in marketing practices. However, the antecedents and consequences of brand experience are still elusive. This model, namely The BRAND EXPE- RESONANCE MODEL, is a new invention of brand experience that could help managers to improve sales particularly in fast food industry. The model is perhaps the first that concentrates on brand experience on resonance and impact on sales of fast food restaurants. Thus far, this model had been used by several fast food restaurants and improved their sales. The BRAND EXPE-RESONANCE MODEL is under filing patent (copyright). Moreover, the findings of the study are published in National Postgraduate Seminar Proceedings, NAPAS 2010, ASEAN Conference on Environment-Behaviour Studies, AcE-Bs 2010 proceedings, ASIAN Environmental-Behaviour Journal, articles accepted from ICSB 2010, ICIMB 2010 and under-review journal Emerald/Scopus and etc.